The Voltage-Dependent Deactivation of the KvAP Channel Involves the Breakage of Its S4 Helix - Bignucolo, Olivier; Bernèche, Simon (Frontiers in Molecular Biosciences, 2020)
Voltage-gated potassium channels allow ion permeation upon changes of the membrane electrostatic potential (Vm). Each subunit of these tetrameric channels is composed of six transmembrane helices, of which the anti-parallel helix bundle S1-S4 constitutes the voltage-sensor domain (VSD) and S5-S6 forms the pore domain. Here, using molecular dynamics (MD) simulations, we report novel responses of the archaebacterial potassium channel KvAP to membrane polarization. We show that the S4 α-helix, which is straight in the experimental crystal structure solved under depolarized conditions (Vm ~ 0), breaks into two segments when the cell membrane is polarized (Vm << 0) , and reversibly forms a single straight helix following depolarization (Vm =0). The outermost segment of S4 translates along the normal to the membrane, bringing new perspective to previously paradoxical accessibility experiments that were initially thought to imply the displacement of the whole VSD across the membrane. The novel model is applied through steered and unbiased MD simulations to the recently solved whole structure of KvAP. The simulations show that the resting state involves a re-orientation of the S5 α-helix by ~ 5-6 degrees in respect to the normal of the bilayer. Our simulations of KvAP reveal that the breaking of S4 under polarization is not a feature unique to hyperpolarization-activated cyclic nucleotide-gated (HCN) channel, as might be suggested by recent cryo-EM structures.